On the importance of asking uncomfortable questions - Dittrich, Alexandre (Perspectivas em Análise do Comportamento, 2023)
In this essay, I briefly present two complementary articles published by Professor José Antônio Damásio Abib in 1993: (1) “‘Is Psychology science?’ What is science?”; (2) “‘Is Psychology science?’ Science is a composite discourse of philosophy, history of science and Psychology”. I point out why the arguments presented in these articles were important for my formation as a radical behaviorist and behavior analyst – and, by extension, why they may be important for the formation of other people. Abib shows that the answers to complex questions, such as those that appear in the titles of his articles, require the combined efforts of several disciplines, both philosophical and scientific. In doing this, he opposes the conformism of immediate, simple and fixed answers, leading us to broaden and deepen the debate. The insistence on questioning and doubting, on skepticism and investigation, characterize Professor Abib’s work, and serve as an example to our community.